Hygrothermal effect on mechanical properties of composite material - Lim, Li Fang (2016)
Fiber-Reinforced Polymer composite material has been a prevalent choice in the marine application over the years. Fiber-Reinforced Polymer is less susceptible to corrosion and its ability to meet a range of requirements through customization has made it popular. Though Fiber-Reinforced Polymer composite is able to reduce the lifecycle cost due to its resistance to corrosion, it is restricted by the material database which made it difficult to predict the reliability and durability of the composite. For this project, it investigates the performance of the hydrothermal aging fatigue behavior of the Bismaleimide Resins (BMI) composite material in prolonged exposure to saline environment through experiments. Three sets of specimens from the same material were prepared. One set was kept dry while the other sets were immersed in artificial seawater at diffusion temperature of 50oC and 80 oC. An array of test was conducted on different sets of specimens to determine the strength and durability of Fiber-Reinforced Polymer composite after diffusion when it undergoes static loading and dynamic loading test. The extended period of immersion of composite material serves as a simulation of the marine environment. The specimen used in this project is HexPly F655, a Bismaleimide Resins composite material manufactured by Hexcel which has a dimension of 250mm by 15mm. The project serves as an addition to the material database of the composite material how the moisture sorption of the Bismaleimide Resins composite material affects the fatigue life of the composite material.